Bureaucracy Pathology in Infrastructure Development of Banjar Village, Sampang Regency - Nur Holifah; Novita Maulida Ikmal; Lutfia Nurul Hidayati (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2022)
This study used bureaucratic theory and bureaucratic pathology to reveal bureaucratic pathologies that occur in villages in the context of infrastructure development that often occurs in Banjar village. The basis of the research used is descriptive qualitative method. The results of this study, firstly, the phenomenon of bureaucratic pathology in infrastructure development in the village of Banjar is still encountered such as frequent discrepancies between the proposals submitted and reports made from the infrastructure development process (incompatibility of budget allocation for infrastructure development). Second, the strategy for rehabilitating bureaucratic pathology in infrastructure development that occurs by gradually monitoring each infrastructure development project that is being worked on, in collaboration with professional and competent construction parties.